Feltáratlan emlékek Kenézy Gyula életéből és munkásságából - Póka, Róbert (Gerundium, 2019)
Unexplored memories from the life and work of Gyula Kenézy. Gyula Kenézy is an outstanding historical figure of the University of Debrecen as well as of the City of Debrecen. Beyond many sculptures, street, prize, a hospital, and a civil society which carry his memories, the cities of Debrecen and Hajdúszoboszló regularly remember the renowned professor. Many monographs gave the account of his life and accomplishments, and a collection of his relics gained a permanent place for commemoration in the Museum of Hajdúszoboszló. Nevertheless, one-hundred years after the beginning of medical education in Debrecen, new pieces of historical records continue to enrich our memories about Gyula Kenézy. For the first time in its history, the Kenézy Memorial Day was organized by the Kenézy Civil Society and the University of Debrecen together in 2017. The program provided us with exciting recollections, and so far unraveled details of the life of Gyula Kenézy.